Student-question-based inquiry in science education. Issue 1 (2nd January 2019) - Herranen, Jaana; Aksela, Maija
ABSTRACT: Students' questions have an important function in science learning, and in inquiry-based approaches. Inquiry teaching in which the students' own questions are used is promising, but a holistic view of the research and practice is lacking. A systematic review was conducted on 30 articles, both research report articles as well as descriptive and evaluative report articles on the use of students' questions as a starting point for inquiry-based science education. The review was carried out using deductive content analysis. This review concentrates especially on the formulation and utilisation of students' questions in inquiry, the benefits of the reported approaches, and the roles that the teacher and the students take during student-question-based inquiry approaches. This review shows that there are various ways to obtain and use students' questions. The results also highlight the teacher's important role in inquiry teaching already in the planning phase. Moreover, the teacher's role is affected by how much emphasise is placed on science learning, and how much value is put on the students' questions. Finally, a model for student-question-based inquiry (the SQBI-model) for science education is presented. This model should be acknowledged also in the teacher education.